COMMUNITY MENTAL HEALTH SERVICES: A WAY FORWARD TO REHABILITATE CHRONIC MENTALLY ILL CLIENT - Tharani, Ambreen; Farooq, Salima; Naveed, Anila (Journal of Ayub Medical College Abbottabad, 2012)
Schizophrenia and other mental illnesses produce devastating effects on a clients' personal and psychosocial wellbeing. Besides the sufferer, it has irrevocable impacts on the lives of their loved ones. With advancement in the treatment modalities, researches have proven that hospital based care and psychotropic drugs are not the sole solution in managing the client symptoms. Deinstitutionalization is the paradigm shift from hospital based to community based care model that allows client/s to spend rest of their lives in the community setting. A well-structured community care based programme that focuses on psychosocial interventions has significant contribution in treatment and rehabilitation of client/s. This article is aimed to provide the evidence of the effective use of community mental health care for management and prevention of relapse of a client with chronic schizophrenia. The substantial evidence of rehabilitation is represented through this case study of a chronic schizophrenic client who received these psychosocial interventions in his own community setting. Keywords: Schizophrenia, community mental health care, psychosocial interventions, rehabilitation